Isolation of Novel and Known Genes from a Human Fetal Cochlear cDNA Library Using Subtractive Hybridization and Differential Screening - Robertson, Nahid G. (1994)
Artículo científico -- Universidad de Costa Rica. Instituto de Investigaciones en Salud, 1994. Este documento es privado debido a las políticas de la revista en la que fue publicado.